An Overview on Different L-Thyroxine (l-T4) Formulations and Factors Potentially Influencing the Treatment of Congenital Hypothyroidism During the First 3 Years of Life - Stagi, Stefano; Municchi, Giovanna; Ferrari, Marta; Wasniewska, Malgorzata Gabriela (Frontiers in Endocrinology, 2022)
Congenital hypothyroidism (CH) is a relatively frequent congenital endocrine disorder, caused by defective production of thyroid hormones (THs) at birth. Because THs are essential for the development of normal neuronal networks, CH is also a common preventable cause of irreversible intellectual disability (ID) in children. Prolonged hypothyroidism, particularly during the THs-dependent processes of brain development in the first years of life, due to delays in diagnosis, inadequate timing and dosing of levothyroxine (l-thyroxine or l-T4), the non-compliance of families, incorrect follow-up and the interference of foods, drugs and medications affecting the absorption of l-T4, may be responsible for more severe ID. In this review we evaluate the main factors influencing levels of THs and the absorption of l-T4 in order to provide a practical guide, based on the existing literature, to allow optimal follow-up for these patients.